EXPERIENCES OF MOTHERS ABOUT THE HOSPITALIZATION OF PREMATURE CHILD - Camila Castro Roso; Regina Gema Santini Costenaro; Rosiane Filipin Rangel; Caren da Silva Jacobi; Claudelí Mistura; Cristiane Trivisiol da Silva; Franciele Roberta Cordeiro; Ana Lúcia Uberti Pinheiro (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/2179769210246 Aim: to describe the experience of mothers in relation to the admission of premature infants in the Neonatal Intensive Care Unit. Method: qualitative research developed with nine mothers whose children were admitted to Neonatal Intensive Care Unit. Data collection occurred during the months of September and October 2008 through semi-structured interviews with open questions. The data were subjected to thematic analysis. Results: with data analysis emerged the following categories: Caring of infant: staying with her mother; and Caring of infant: challenges faced by mothers during hospitalization. Conclusions: provide the link through attachment, the care provided by the mother, feeding, affection, lap, hug, among others, is essential at this stage of the family life. The nursing can help in promotion of health and quality of life for premature infants and families through strategies that include them in care.